Kategoryzacja w dyskursie zaburzonym – nazwy własne a nazwy pospolite - Gliwa-Patyńska Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Cel badania: ocena możliwości dokonywania kategoryzacji semantycznej nazw pospolitych i nazw własnych przez osobę ze zdiagnozowaną afazją nominacyjną. Metoda: w badaniu wykorzystano podejście kliniczno-eksperymentalne. Wyniki poddano analizie jakościowej oraz ilościowej. Wyniki: wskazano najlepiej zachowane relacje semantyczne, określono zjawiska świadczące o jakości dostępu do słownika mentalnego, wyszczególniono objawy degradacji słownika semantycznego, ustalono, na którym etapie przetwarzania dochodzi do zaburzeń. Ocena ilościowa obejmowała procentowy opis uzyskanych wyników. Wnioski: obserwowano ogólnie lepszą umiejętność badanej w identyfikacji kategorialnej nazw własnych aniżeli nazw pospolitych. Wiązać to zapewne można ze wspomnianą specyfiką nazw własnych, powiązaną z ich entropią informacyjną. Można mówić o kilku przyczynach obserwowanych dysfunkcji. Najistotniejszy wydaje się deficyt językowy przejawiający się zaburzeniami dostępu do słownika semantycznego, dysfunkcjami w zakresie operacji metajęzykowych w obrębie sieci semantycznych, trudnościami z aktualizacją słów i w pewnym zakresie zubożeniem zasobów leksykonu mentalnego. Wyniki testu z pewnością należy rozpatrywać także w kontekście dysfunkcji w obszarze poznawczym.

Aim of the study: the aim of the study was to assess the possibility of making a semantic categorization of common names and proper names by a person diagnosed with appointment aphasia. Method: the study used a case-experimental approach. The results were analyzed qualitatively and quantitatively. Results: the best-preserved semantic relations were indicated, the phenomena proving the quality of access to the mental dictionary were determined, the symptoms of degradation of the semantic dictionary were specified, the stage of processing disturbed was determined. The quantitative evaluation included the percentage description of the obtained results. Conclusions: A generally enhanced ability of the respondent to identify categorical proper names than common names was observed. This can probably be associated with the aforementioned specificity of proper names, related to their information entropy. We can talk about several causes of the observed dysfunctions, the most important seems to be the language deficit, manifested by impaired access to the semantic dictionary, dysfunctions in the field of metalinguistic operations within semantic networks, difficulties with updating words and, to some extent, the depletion of the resources of the mental lexicon. The test results should certainly also be considered in the context of cognitive dysfunctions. The results of this research are in accordance with previous findings suggesting that the difficulty of semantic categorization is related to the dysfunction of semantic memory in the field of categorization of the so-called fuzzy concepts.
Categorization in a disturbed discourse – proper names and common names
Keywords: nazwy własne; nazwy pospolite; afazja; kategoryzacja; słownik semantyczny; proper names; common names; aphasia; categorization; semantic dictionary